2006
DOI: 10.1021/ac0614644
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Quantum Dots Fluorescence Resonance Energy Transfer-Based Probes for Enzymatic Activity and Enzyme Inhibitors

Abstract: The paper describes the development and characterization of analytical properties of quantum dot-based probes for enzymatic activity and for screening enzyme inhibitors. The luminescent probes are based on fluorescence resonance energy transfer (FRET) between luminescent quantum dots that serve as donors and rhodamine acceptors that are immobilized to the surface of the quantum dots through peptide linkers. Peptide-coated CdSe/ZnS quantum dots were prepared using a one-step ligand exchange process in which RGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 31 publications
2
101
1
2
Order By: Relevance
“…[363,371] Scheme 5.2: Two-step FRET mechanism (adapted from reference [363] Moreover, some groups reported the application of FRET between II-VI QDs and fluorescent dyes linked together by different biomolecules such as antibody, [369,373,378] BSA, [374,377] peptide, [367,375,376,382,383] and DNA [379][380][381].…”
Section: Chapter 5 Bioluminescence Resonance Energy Transfer (Bret) mentioning
confidence: 99%
See 1 more Smart Citation
“…[363,371] Scheme 5.2: Two-step FRET mechanism (adapted from reference [363] Moreover, some groups reported the application of FRET between II-VI QDs and fluorescent dyes linked together by different biomolecules such as antibody, [369,373,378] BSA, [374,377] peptide, [367,375,376,382,383] and DNA [379][380][381].…”
Section: Chapter 5 Bioluminescence Resonance Energy Transfer (Bret) mentioning
confidence: 99%
“…Bioluminescence resonance energy transfer (BRET) with PbS quantum dots 90 the peptide linker. [382,383] …”
Section: Chapter 5 Bioluminescence Resonance Energy Transfer (Bret) mentioning
confidence: 99%
“…Since semiconductor nanoparticles or quantum dots are strongly fluorescent, they are widely used in FRET-based techniques. [5][6][7][8][9][10][11][12][13][14] CdSe/ZnS quantum dot-aptamer conjugates are used in targeted cancer imaging, sensing, and therapy based on FRET. 5 Cds/ZnS quantum dots can be used as protease sensors by employing FRET.…”
Section: Introductionmentioning
confidence: 99%
“…Other dye-labeled biological molecules such as peptides, DNA, RNA, or aptamers that are responsive to enzymes, drugs, or other chemicals can be easily adapted to this format and indeed a few preliminary qualitative enzymatic studies using QD-substrates have been reported, including a QD-sensor for monitoring lactamase activity associated with antibiotic resistance [55][56][57][58]. With the large number of putative proteases in the human genome (∼560) as well as those utilized by pathogens, many will require intact protein substrates for recognition and cleavage/digestion [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%